2013
DOI: 10.1007/s10096-013-1952-3
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of carbapenem resistance mechanisms in VIM-2-producing Pseudomonas aeruginosa under selective pressure

Abstract: Pseudomonas aeruginosa has the potential to achieve resistance to carbapenems via the acquisition of carbapenemase-encoding genes, the downregulation of the OprD porin, the overexpression of efflux systems and the overproduction of cephalosporinases. One hundred and fifty carbapenem-non-susceptible isolates from 2008 to 2010 were screened for carbapenemase production, OprD porin loss, efflux pumps overexpression and inducible AmpC beta-lactamase production. For comparison reasons, the presence of the same mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…The variations in the results of the antibiotic resistance might be referred to the difference in the pattern of drug use in different parts of the world and due to the several mechanisms that have been reported for P. aeruginosa, including: 1) Reduced expression or loss of OprD porin causing reduced antibiotic permeability, 2) Overexpression of MexAB-OprM pump which increases antibiotic ef lux, 3) Production of β-lactams and aminoglycosides inactivating enzymes, 4) Mutations of gyrases and topoisomerases which cause luoroquinolone resistance. These mechanisms in combination lead to multiple drug resistance [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the results of the antibiotic resistance might be referred to the difference in the pattern of drug use in different parts of the world and due to the several mechanisms that have been reported for P. aeruginosa, including: 1) Reduced expression or loss of OprD porin causing reduced antibiotic permeability, 2) Overexpression of MexAB-OprM pump which increases antibiotic ef lux, 3) Production of β-lactams and aminoglycosides inactivating enzymes, 4) Mutations of gyrases and topoisomerases which cause luoroquinolone resistance. These mechanisms in combination lead to multiple drug resistance [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that carbapenemresistant Gram-negative nosocomial pathogens will continue to evolve accumulating more carbapenem-resistance mechanisms [Meletis et al 2014b], or more than one carbapenemase-encoding gene [Meletis et al 2015a]. This will lead in many cases to increased carbapenem MICs ruling out the best-to-date therapeutic choice against carbapenemase producers, which is the combined treatment including at least one carbapenem.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, the accumulation of carbapenem-resistant mechanisms could probably further increase carbapenem MICs, leaving even fewer therapy options for clinicians against the multi-drug resistant P . aeruginosa [ 3 ]. Studies on the antimicrobial resistance in P .…”
Section: Introductionmentioning
confidence: 99%